2020
DOI: 10.36198/9783838554990
|View full text |Cite
|
Sign up to set email alerts
|

Das St. Galler Management-Modell

Abstract: Organisationale Wertschöpfung wird zunehmend komplexer. Das St. Galler Management-Modell präsentiert dafür zwei Perspektiven: Die Aufgabenperspektive erörtert die Gestaltungsfelder einer integrativen Management-Praxis im Zusammenspiel von Umwelt, Organisation und Management. Die Praxisperspektive beleuchtet die Voraussetzungen einer wirksamen und verantwortungsbewussten Management-Praxis. Diese neueste Fassung des St. Galler Management- Modells integriert alle bisherigen Versionen des SGMM und legt ein besonde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, in the field of sustainable BM and CBM research connected with organizational ambidexterity, large unexplored research territories can be found. Given the obvious uncertainties, financial risks, and organizational paradoxes (Hofmann & Jaeger‐Erben, 2020) that emerge with the institution of such lifeworld laboratories, incumbents need long‐term reflection and innovation partnerships against the backdrop of transdisciplinary and action‐based research approaches (Rüegg‐Stürm & Grand, 2016). The co‐production of knowledge for circular literacy (Zwiers et al, 2020) through the collaboration of actor groups from academics and businesses encourages mutual learning processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the field of sustainable BM and CBM research connected with organizational ambidexterity, large unexplored research territories can be found. Given the obvious uncertainties, financial risks, and organizational paradoxes (Hofmann & Jaeger‐Erben, 2020) that emerge with the institution of such lifeworld laboratories, incumbents need long‐term reflection and innovation partnerships against the backdrop of transdisciplinary and action‐based research approaches (Rüegg‐Stürm & Grand, 2016). The co‐production of knowledge for circular literacy (Zwiers et al, 2020) through the collaboration of actor groups from academics and businesses encourages mutual learning processes.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational processes, which cannot be mapped by tool kits or static business design approaches, must also be reformed (Amit & Zott, 2020; Evans et al, 2017; Massa et al, 2018; Parrish, 2010; Roome & Louche, 2016; Thomke, 2020). CBM innovation can be difficult to accurately predetermine and be controlled by management, as firms as social systems are simultaneously stable and dynamic in their emergence, subject to a plethora of opportunities, and are shaped by creative moments (Foss & Saebi, 2015; Rüegg‐Stürm & Grand, 2016). Therefore, “companies must adopt an effectual attitude toward business model experimentation” (Chesbrough, 2010, p. 362) to deal with volatility, uncertainty, complexity, ambiguity (VUCA; Bennis & Nanus, 1985) and contingency of organizational evolution.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that organizations do not exist in isolation, but are in a reciprocal relationship with their environment (Luhmann and Baecker 2018). This is put into practice, for example, by the St. Gallen fourth generation Management Model (Rüegg-Stürm and Grand 2015): the mediation between the inside of the organization and the environment is considered as the central function of management. Value creation is directly dependent on successful communication between the inside and outside (Theis-Berglmair 2013: 34) and management can be seen as a bundle of communicative tasks.…”
mentioning
confidence: 99%
“…Value creation thus is directly dependent on successful communication between the inside and outside (Stücheli-Herlach et al 2017). Management is therefore a communicative practice that is implemented in a specific way in relation to the environment, more precisely, the various spheres of environment (Rüegg-Stürm and Grand 2015).…”
mentioning
confidence: 99%